2018
DOI: 10.17650/2222-8721-2018-8-1-38-45
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Boston Carpal Tunnel Questionnaire in Russia

Abstract: : Yusupova D.G., Suponeva N.A., Zimin A.A. et al. Validation of the Boston Carpal Tunnel Questionnaire in Russia. Nervnomyshechnye bolezni = Neuromuscular Diseases 2018;8(1):38-45.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
1
1
3
Order By: Relevance
“…The Bulgarian version of BCTQ showed a high reliability index, expressed by Cronbach's alpha coefficient and reproducibility of results. Cronbach’s alpha values reported by other authors differ, but as in our study, they are above 0.8 for both scales [ 4 - 9 , 15 ]. The degree of reproducibility of the results in our study exceeds that of many other studies; the Russian version has a coefficient of 1 [ 15 ].…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The Bulgarian version of BCTQ showed a high reliability index, expressed by Cronbach's alpha coefficient and reproducibility of results. Cronbach’s alpha values reported by other authors differ, but as in our study, they are above 0.8 for both scales [ 4 - 9 , 15 ]. The degree of reproducibility of the results in our study exceeds that of many other studies; the Russian version has a coefficient of 1 [ 15 ].…”
Section: Discussioncontrasting
confidence: 74%
“…The study of criterion validity using the translated and validated DASH questionnaire is widely used in the validation of BCTQ [7,15,16]. In all of them, as in our study, a strong or very strong correlation has been found between the scores obtained from the two questionnaires.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Валидность бывает содержательной и критериальной. Содержательную валидность, отражающую, насколько опросник в целом и каждый из его компонентов охватывают заложенные в нем характеристики, исследовали путем экспертной оценки [18] Всем пациентам в плановом порядке была выполнена эндоскопическая декомпрессия срединного нерва в нейрохирургическом отделении Научного центра неврологии. Ранее на базе нейрохирургического отделения проведены разработка и детализация оперативного лечения, определена оптимальная техника выполнения декомпрессии срединного нерва (патент № 2615905 «Способ декомпрессии срединного нерва при карпальном туннельном синдроме»).…”
Section: оригинальные исследованияunclassified
“…Для оценки выраженности симптомов и функциональных нарушений при КТС удобным в практике является использование Бостонского опросника (Boston Carpal Tunnel Questionnaire, BCTQ), разработанного D. W. Levine и соавт. в 1993 г. для стандартизации результатов клинического обследования при данном заболевании, в том числе при оценке в динамике [4,5].…”
Section: Introductionunclassified